STUDI KRITIS TERHADAP KRITIK NALAR ARAB MUHAMMAD ABED AL-JABIRI - Mustofa, Imam (STAIN Jurai Siwo Metro, 2010)
AbstractThis article traits to discuss Mohammad Abed al-Jabiris critical Arab reason project. As result of study, the author found that Al-Jabiri projected his self in the specific ideas project. He tried to build and bring Islam to improvement based on reality. He poured building of epistemology to three concepts